Design of energy efficient control unit and implementation on high performance FPGA - Yousef A. Baker, El-Ebiary; Keshav, Kumar; Bishwajeet, Pandey (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
With the crisis of power across the globe, green communication and power-efficient devices are getting more and more attention. This work emphasis about the implementation of Control Unit (CU) circuit on FPGA kit. In this project, power consumption of CU circuit is analyzed by changing the different Input/Output (I/O) standards of FPGA. This project is implemented on Xilinx 14.1 tool and the power consumption on CU is calculated with X Power Analyzer tool on 28-Nano-Meter (nm) Artix-7 Field Programmable Gate Array (FPGA). Out of different I/O standards, CU circuit is most power efficient with LVCMOS I/O standard on Artix-7 FPGA.